B(a-c)-x(a-c)-2(a-c)=(a-c)(b-x-2)
[tex]6.3 + 3 \times ( - 1.1) = 6.3 + ( - 3.3) = 6.3 - 3.3 = 3
250+75=325
385-325=60
Ответ:вторая бригадавыловила больше на 60 ц
- 3,5 = - 3 5/10 = - 3 1/2
----------------------------------
х - ( 7 5/9 - 5 1/6) = - 3,5
х - (7 10/18 - 5 3/18) = - 3 1/2
х - 2 7/18 = - 3 1/2
х = - 3 1/2 + 2 7/18
х = - (3 9/18 - 2 7/18)
х = - 1 2/18
х = - 1 1/9
--------------------------------
Проверка: - 1 1/9 - (7 10/18 - 5 3/18) = - 3 1/2
- 1 2/18 - 2 7/18 = - 3 1/2
- 3 9/18 = - 3 1/2
- 3 1/2 = - 3 1/2